Perancangan Aplikasi Inventory Control PT. Kimia Farma Apotek - Alqomari Cahyo (Universitas Indraprasta PGRI Jakarta, 2020)
PT. Kimia Farma Apotek engaged in the distribution of and market in healthcare products is one of companies that has not used a computerized system in terms of controlling inventory so that it often makes errors in and inaccuracies of the goods collection, resulting in the running out of goods before reordering. The purpose of this research is to design an inventory control application using the Java programming language and applying research and development methods that can produce certain products and test the effectiveness of those products. The developed application can make it easier for employees to control inventory more effectively and efficiently.